Politics of intellectual property rights: the case of Malaysia-US free trade agreement - Moniruzzaman, Md. (Medwell Publishing, 2016)
Bilateral free trade agreement (FTA) has been an increasing trend over the past decades. Highly developed countries are getting into FTA with the emerging economies in order for maintaining competitive advantage. A particular area of such agreement is intellectual property rights (IPRs) in superior technology and research. The bone contention of the ongoing Malaysia-US free trade negotiation has been the IPRs. This article looks at the central issues of the negotiation process. It contends that both Malaysia and USA are concerned with their political priorities conditioned by their domestic necessities that influence the negotiation and signing of an agreement. The United States resorts to bilateral and multilateral means to impose its priorities, while Malaysia asserts its national interests with domestic economic and political priorities.